Mentoring the Implementation of In-Depth Learning for High School and High School Plus Teachers at the Al-Ashriyyah Nurul Iman Foundation - Tjalla, Awaluddin; Rahayu, Wardani; Sarifah, Iva; Ridwan, Achmad; Riyadi, Riyadi; Priyanto, Sugeng; Rini, Indah Mustika; Merrydian, Siska (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This community service program was conducted in the framework of strengthening the professional competencies of high school teachers in the application of Deep Learning strategies. The target audience were teachers of SMA and SMA Plus at Yayasan Al-Ashriyyah Nurul Iman Islamic Boarding School – Parung, Bogor. The problems found included the lack of understanding and implementation skills related to deep learning-based learning strategies and assessment instruments. Through workshops, mentoring, and collaborative coaching methods, the teachers were guided to design and apply deep learning-based assessments. The results indicated an improvement in teachers' understanding and ability to implement deep learning assessments, as reflected in positive feedback in the satisfaction survey, the increased post-test scores and formation of professional traits based on teachers’ self-assessment. This program contributes significantly to pedagogical strengthening and the quality of learning in the Merdeka Belajar curriculum context.